Changes in Heart Rate of Pitchers during Semi-Hard Baseball Practices and Matches. Issue 3 (December 2014) - Hashimoto, Yasuhiro; Inomata, Kimihiro
High heart rate during competition is a response to both psychological and physiological stress, making it difficult to examine psychological stress in sport. The validity of a new method to extract psychological stress by subtracting heart rate during practice from that of competition was evaluated. The method was used in actual competition for eight pitchers. Most participants showed a "coasting phase, " "increment phase, " and "descent phase" for heart rate time-series data under both conditions. Heart rate in competitions was higher than during practice, and heart rate in both conditions showed a high correlation. Heart rate changes were significantly higher in situations in which two or three balls had already been thrown compared to zero balls thrown. Thus, psychological stress can be examined in various competition conditions using this method.